Cyclosporine Eye Emulsion Vs Loteprednol Etabonate Eye Drops for the Management of Subepithelial Infiltration Linked to Adenoviral Keratoconjunctivitis: Doi: 10.36351/pjo.v41i4.2160 - Luay Kadhim, Sura; Kamel Al-Jenabi, Ziyad (Pakistan Journal of Ophthalmology, 2025)
Purpose: To compare the effectiveness of cyclosporine eye emulsion versus Loteprednol etabonate eye drops in the management of subepithelial infiltrates (SEIs) secondary to adenoviral keratoconjunctivitis(AKC). Study Design: Quasi experimental study. Place and Duration of Study: Al-Kindy Teaching Hospital in Baghdad from January 2024 to December 2024. Methods: Sixty-nine patients with confirmed multifocal SEIs were enrolled and assigned to either cyclosporine (n=35) or Loteprednol (n=34) group by convenient sampling. Patients were monitored over 6 months using slit-lamp biomicroscopy and non-contact tonometry to assess treatment outcomes, side effects, and recurrence. Data was analyzed using SPSS version 26. Descriptive statistics (frequency and percentage) were used for numerical data. The Chi-square test was applied to compare categorical variables such as age groups, gender distribution, side effects, and recurrence rates. Independent sample t-tests were used to compare continuous variables, including IOP between the groups. A p-value < 0.05 was considered statistically significant. Results: Loteprednol demonstrated faster SEI clearance at 2 and 4 months (P < 0.05), with higher rates of complete corneal clarity by month 4. However, it also showed significant rise in IOP and a higher recurrence rate (20.6%) compared to cyclosporine (8.6%) at 6 months. Cyclosporine was associated with more early ocular discomfort but offered better long-term control and lower relapse. Conclusion: Loteprednol provides faster symptomatic relief, whereas cyclosporine offers more durable outcomes with fewer recurrences. Sequential therapy, starting with corticosteroids and transitioning to cyclosporine, may optimize AKC management and further investigation warrants.